Community risk perception of Mpox in Osun State, Southwest Nigeria - Mariam Treasure Olaoye; Mathias Besong; Joseph Tanimowo; Abosede Olatokun; Ayodele Majekodunmi (Journal of Interventional Epidemiology and Public Health)
Background: Mpox, formerly known as Monkeypox, is a viral zoonotic disease that re-emerged in Nigeria in September 2017. Since then, all states around Osun have reported at least one case. However, Osun State reported her first incidence on August 15, 2022. We conducted a community risk assessment in response to the outbreak to assess the risk of disease and determine communication needs.